Aligned magnetic field on dusty casson fluid over a stretching sheet with newtonian heating - Arifin, Nur Syamilah; Mohd Zokri, Syazwani; Mohd Kasim, Abdul Rahman; Salleh, Mohd Zuki; Yusoff, Wan Nur Syahidah; Mohammad, Nurul Farahain; Shafie, Sharidan (Penerbit UTM Press, UTM, 2017)
Boundary layer flow and heat transfer on Casson fluid with dust particle over a stretching sheet is numerically investigated. The influences of aligned magnetic field together with Newtonian heating are considered in this problem. The governing equations are first transformed into ordinary differential equations using the appropriate similarity transformation variables. The numerical computation using Runge-Kutta Fehlberg (RKF45) method is employed to generate the results. Several physical parameters for both phases (fluid and particle) such as aligned angle, magnetic field parameter, Casson parameter, fluid particle interaction parameter, Prandtl number and conjugate parameter are investigated and analysed. The results in term of distribution velocity and temperature are presented graphically. The finding revealed that a rise in aligned angle and magnetic field parameter led to decrease the velocity profile and increase the temperature profile for both phases.